ANTICIPATION MEASURES FOR COPYRIGHT INFRINGEMENT OF VIDEO IN DIGITAL PLATFORM : Tindakan Antisipasi Terhadap Pelanggaran Hak Cipta Video Pada Platform Digital - Ramadhan, Galih Dwi; Nugroho, Krisna Akbar; An Ni’am , Fathir (JIPRO: Journal of Intellectual Property, 2025)
Digital platforms become a place to enjoy copyrighted digital content that is widely distributed in cyberspace, and cyberspace becomes a digital space that connects various digital platforms through the Internet network. Copyright as a legal instrument to protect any copyrighted material. Cinematography, which is also known as video, is a material object protected by copyright. The primary research focus is resolving video copyright infringement on digital platforms and determined measures for video copyright infringement on digital platforms. This research uses a normative method with a juridical approach. The results of this study understand the concept of copyright infringement of video content on digital platforms based on Indonesian copyright law and design anticipatory measures in form of proactive action of creators and utilization copyright service features in digital platform, then enforcement measures for copyright infringement of video in digital platform by takedown content, report to authorized institutions and utilize online dispute resolution, as an initial measures before taking a legal remedy under copyright law.